(3hSGFd GdSGFd Edi eYQaI GdChGFds - (3eMeO Hf eMhO Hf eMeO CHj GddWa GdebOSjs
(3ChdgG (B:s
(3bGd eMeO aJi GHf GdTeS GHf CHj GddWa GdabjQ GdebOSi CMeO eG bOe di HGdJbQjQ MeO GdbOje GdChd GdbOjQ GdbOje GdCMO ehVM efgG L GdgOi ddegJOi s
(3BNQgG (B:s
(3hHOhGjI CeI EdjgG JONd GeJg GdZQGA hajgG jhcd ef GdWYGe HOA GdRjGOI ef cHO GdMhJ ceG CaGOg hGdMeO ddg Ydi eG jSQ ef Pdc fXekG ChdkG hBNQkG Je cJGH hSGFd GdSGFd ai eYQaI GdChGFd HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdeLGejYs